Dominating Role of Aligned MoS2/Ni3S2 Nanoarrays Supported on Three-Dimensional Ni Foam with Hydrophilic Interface for Highly Enhanced Hydrogen Evolution Reaction - Cao, Jiamu; Zhou, Jing; Zhang, Yufeng; Wang, Yuxi; Liu, Xiaowei (ACS applied materials & interfaces, 2018)
When using water splitting to achieve sustainable hydrogen production, low-cost, stable, and naturally abundant electrocatalysts are required to replace Pt-based ones for the hydrogen evolution reaction (HER). Herein, for the first time, a novel nanostructure with one-dimensional (1D) MoS2/Ni3S2 nanoarrays directly grow on a three-dimensional (3D) Ni foam is developed for this purpose, showing excellent catalytic activity and stability. The as-prepared 3D MoS2/Ni3S2/Ni composite has an onset overpotential as low as 13 mV in 1 M KOH, which is comparable to Pt-based electrocatalyst for HER. According to the classical theory, the Tafel slope of the new composite is relatively low, as it goes through a combined Volmer–Heyrovsky mechanism during hydrogen evolution. All the results attribute the excellent electrocatalytic activity of the nanostructure to the electrical coupling among Ni, Ni3S2, and MoS2, the super hydrophilic interface, the synergistic catalytic effects produced by the MoS2/Ni3S2 nanoarrays, and abundant exposed active edge sites. These unique and previously undeveloped characteristics of the 3D MoS2/Ni3S2/Ni composite make it a very promising earth-abundant electrocatalyst for HER.